Evaluasi Dan Modifikasi Pola Tata Tanam Daerah Irigasi Prako Berdasarkan Ketersediaan Air - Saidah, Humairo; Supriyadi, Anid; Wiradarma, Lalu Wirahman (LPPM Universitas Mataram, 2024)
Prako Weir in East Lombok Regency has limited water availability, which affects its ability to serve the provision of irrigation water. Failure to meet irrigation water needs is increasingly felt, so adaptation steps are needed to reduce more significant losses at the farmer level. This study aims to evaluate the current cropping pattern and obtain alternative cropping patterns that are more appropriate according to water availability in Prako Weir to minimize the potential for farmer crop failure. The study began by analysing water availability by calculating the mainstay discharge using a ranking method using Prako Weir discharge data. Continued analysing water requirements in the current cropping pattern and several alternative cropping patterns using the KP-01 method. Furthermore, the best cropping pattern was selected using the water balance method. The results obtained were the best cropping pattern according to the water availability pattern in Prako Weir, namely Rice-Soybeans-Soybeans, which began planting in early October, with an annual water surplus of 775.24 l/second. Meanwhile, the current cropping pattern, Rice-Rice-Soybeans, shows an annual deficit of 625.31 lt/second. However, if economic considerations are used, then the current planting pattern is still acceptable even though it is at risk of being unable to meet its water needs. However, a solution can be taken by providing water in turns.